Ruled reading and Biblical criticism - Bell, Matthew T. (Journal of theological interpretation supplements, 2019)
Communion, canon, and the Bible of the Church -- Ontology of scripture and indwelling salvation's epic (or, whose identity story?) -- The legacy of modernity and the methodological (pre?)occupations of a critical age -- A case study in "postmodern" ruled reading -- Ruled reading in the unfolding epic : concluding reflections on the arts of homily and devotional criticism.